HORMONAL AXES AND METABOLIC HOMEOSTASIS IN WOMEN: PHYSIOPATHOLOGICAL BASES AND CLINICAL IMPLICATIONS - Pimenta, Luís Ricardo de Lima; da Costa, Anna Catharinna; Machado, Herion Alves da Silva; Silva, Luciene dos Santos; Cerqueira, Maria Clara Nascimento; Valentim, Jeniffer de Souza; Moreira, Kariny Rezende; da Silva, Ismael Rodrigues; Freire, Emanuelly Vitória Santos; Nunes, Vanessa dos Santos; de Souza, Marta Alencar Alves (Seven Editora, 2026)
Hormonal axes play a fundamental role in maintaining female metabolic homeostasis, forming a complex and interdependent network that integrates reproductive, metabolic, hepatic, and psychoneuroendocrine functions. This study aimed to analyze the pathophysiological basis of the main hormonal axes involved in female metabolic regulation and their clinical implications throughout the reproductive cycle. This is an integrative literature review, conducted in international databases, encompassing publications between 2021 and 2026. Original studies, systematic reviews, and meta-analyses addressing the interaction between metabolism and female hormonal regulation were included. The results showed that metabolic hormones, such as insulin and leptin, exert a direct influence on the hypothalamic-pituitary-gonadal axis, impacting ovulation and fertility. Obesity and insulin resistance were associated with hyperandrogenism, ovulatory dysfunction, and worse outcomes in assisted reproduction. Thyroid dysfunctions, even subclinical ones, have been linked to menstrual irregularities and an increased risk of pregnancy loss. Chronic activation of the hypothalamic-pituitary-adrenal axis has been associated with menstrual cycle alterations and increased vulnerability to mood disorders. Furthermore, the interaction between the ovary and liver has proven relevant in modulating hormone bioavailability and susceptibility to metabolic disorders. It is concluded that female metabolic homeostasis depends on the dynamic integration of multiple hormonal axes and environmental factors, with dysregulation of these systems associated with significant clinical repercussions. An integrated, preventive, and multidisciplinary approach is essential for promoting women’s hormonal and metabolic health.